2014
DOI: 10.1111/cobi.12336
|View full text |Cite
|
Sign up to set email alerts
|

Problems with mitigation translocation of herpetofauna

Abstract: Mitigation translocation of nuisance animals is a commonly used management practice aimed at resolution of human-animal conflict by removal and release of an individual animal. Long considered a reasonable undertaking, especially by the general public, it is now known that translocated subjects are negatively affected by the practice. Mitigation translocation is typically undertaken with individual adult organisms and has a much lower success rate than the more widely practiced conservation translocation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(115 citation statements)
references
References 46 publications
7
103
0
5
Order By: Relevance
“…Studies overseas have shown that mitigation-driven translocations of reptiles have high failure rates (Germano & Bishop 2009;Germano et al 2015;Sullivan et al 2015). This review has identified some areas of concern about mitigation-driven translocations of lizards in New Zealand.…”
Section: Concerns About Mitigation-driven Translocationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies overseas have shown that mitigation-driven translocations of reptiles have high failure rates (Germano & Bishop 2009;Germano et al 2015;Sullivan et al 2015). This review has identified some areas of concern about mitigation-driven translocations of lizards in New Zealand.…”
Section: Concerns About Mitigation-driven Translocationsmentioning
confidence: 99%
“…If the habitat is at carrying capacity, then it is likely that released animals will either die or displace resident lizards (Sullivan et al 2015). If the habitat is below carrying capacity, but the refuges that offer protection from predation are fully occupied, the translocated individuals will be vulnerable to predation by introduced mammals (Norbury et al 2014b).…”
Section: Concerns About Mitigation-driven Translocationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other species with high site fidelity and small home ranges within energy installations will be more vulnerable, especially those that are sensitive to disturbance and do not prosper when the subject of translocation efforts (Sullivan et al . , but see Brand et al . ).…”
Section: Concept 2: There Are “Winner” and “Loser” Species In Usse Ecmentioning
confidence: 99%